Comparative toxicokinetics and tissue distribution of prothioconazole and prothioconazole-desthio in Chinese lizards (Eremias argus) and transcriptional responses of metabolic-related genes. (April 2019) - Xie, Yun; Li, Leon Yu Zheng; Hao, Weiyu; Chang, Jing; Xu, Peng; Guo, Baoyuan; Li, Jianzhong; Wang, Huili
Abstract: Prothioconazole (PTC) is a widely used triazolinthione fungicide with low toxicity and short residual period. However, its desulfurization metabolite, prothioconazole-desthio (PTC-d), is more persistent and has higher toxicity in terrestrial animals. In this study, the toxicokinetics (TK) and tissue distribution of PTC and PTC-d in Chinese lizards ( Eremias argus ) were measured following single oral dose (100 mg kg −1 body weight) treatments. TK parameters indicated that PTC was more rapidly absorbed than PTC-d, as indicated by its shorter time to reach peak concentrations in most tissues. Furthermore, the relative bioavailability of PTC in lizards was lower than that of PTC-d. Compared with PTC, PTC-d preferentially accumulated in lizards, as reflected by longer half-life of PTC-d. During the distribution process, PTC-d generated in vivo was transported from other tissues and was deposited in the skin and tail, where PTC-d may be excreted by exuviation or tail detachment. Preferential enrichment of S-enantiomer of both PTC and PTC-d were observed in all tissues. Hepatic cytochrome P450 gene expression measurement revealed that cyp1a5 and cyp3a28 exhibited the strongest responses in both treatment groups. In addition, the opposite responses of cyp2k4 in different treatment groups may indicate that this enzyme caused differences in the rates of metabolism of the two chemicals. This study compared the TK profile of PTC and its desulfurization metabolite PTC-d in lizards and demonstrated that the desulfurization of PTC could increase its ecological risk due to the higher bioavailability and persistence of PTC-d. Graphical abstract: Image 1 Highlights: The bioavailability of PTC-d is higher than its parent compound PTC in lizards. PTC-d is excreted slower than PTC in lizards. Both chemicals displayed S-biased accumulation in lizards. PTC-d generated in vivo can be transported from other tissues to the skin and tail. Abstract : Risk assessments should place greater emphasis on prothioconazole-desthio than on prothioconazole due to the higher bioavailability and persistence of the former.